Life Cycle of Wild Silkmoth Attacus atlas L. Fed on Mahogany Leaves and Soursop Leaves - Hani Rahmawati; Juli Rochmijati Wuliandari (Jurnal Biologi Tropis, 2023)
The study aims to investigate the life cycle and success of the Attacus atlas L. larvae fed with mahoni leaves and sirsak leaves. Observations are done on the development of larvae from eggs until they reach the adult butterfly phase. The study was conducted between November 2022 and January 2023 using direct observation methods to look at the life cycle of Attacus atlas L. Observations were carried out in the morning and in the evening. Data on the success rate of life of larvae in each stage of development is also recorded. Research has shown that the life cycle of A. atlas L. larvae on mahoni leaf foods has a shorter phase period compared to sirsak leaf feed. The age of the A. atlas L. larvae tends to be higher when feeding the sirsak leaves, especially in the subsequent instar phase. However, further research is needed to gain a more comprehensive understanding of the other factors that affect the success of the life of A. atlas L. larvae on various types of feed. This research contributes to the biological understanding and management of A. atlas L. larva conservation, as well as providing important insights into the conservation efforts of this species as a wild silk insect that has significant economic value.